Walking through virtual mazes: Spontaneous alternation behaviour in human adults. (June 2020) - Rothacher, Yannick; Nguyen, Anh; Lenggenhager, Bigna; Kunz, Andreas; Brugger, Peter
Abstract: Spontaneous alternation behaviour (SAB) is the tendency to systematically alternate directional choices in successive maze arms. Originally discovered in rats, SAB has been extensively investigated in a broad range of species. In humans, however, SAB has been mostly ignored, possibly due to the difficulties arising from the use of life-size mazes. We here propose to close this gap by advancing the study of human SAB by use of virtual reality (VR). Alternation rates in humans were examined in three experiments, each deploying a specific type of virtual maze. The three virtual mazes tested 1) the effect of a concurrent cognitive task on baseline alternation rates, 2) the differential influence of locomotor and visual factors on alternation behaviour, and 3) the direction alternation in an unrestricted open space. We report a general tendency in adult human walkers to alternate walking directions in the classical T-maze context. The search for an effect of a concurrent cognitive task and the influence of locomotor and visual factors on alternation behaviour remained inconclusive. No evidence for alternation behaviour in an open space was found. Together, the experimental series elucidates the presence and characteristics of SAB in humans and paves the way for the systematic study of its neurocognitive basis.